Use of ′Mishri′ A smokeless form of tobacco during pregnancy and its perinatal outcome - Pratinidhi Asha; Gandham Sudesh; Shrotri Aparna; Patil Archana; Pardeshi Shrikar (Wolters Kluwer Medknow Publications, 2010)
Background: Use of ′Mishri′ (Tobacco containing teeth cleaning powder) is common in the central and southern part of India. Objectives: To study the effects of Mishri use on the fetus during pregnancy and the perinatal outcome, and stopping its use. Materials and Methods: All apparently healthy pregnant women were enrolled at 20 weeks of gestation from rural Maharashtra, India. Information related to use and giving up of Mishri, previous obstetrical history, current pregnancy, delivery and outcome during the perinatal period were recorded. Appropriate tests of significance were applied. Results: Out of 705 enrolled pregnant women, 218 (30.9%) were using Mishri. The proportion of women with complications during the previous perinatal period, complaints and complications during the current pregnancy/delivery and the number of stillbirths were significantly more among Mishri users. A relative risk of abnormal delivery was 2.7 for the users. In spite of counseling, 153 women never stopped the use of Mishri and gave birth to babies weighing on an average 169.9 gm less (statistically significant) than babies born from the group that never used it. Babies of 28.8% who stopped/reduced consumption of Mishri were significantly benefited. Conclusions: The improvement seen in babies born to 28.8% mothers who stopped/reduced consumption of Mishri by 32 weeks during the current pregnancy is of paramount importance in the developing world for primary prevention of low birth weight.